Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur - Stavanny Inri, Yanti (Jurnal Paradigma Akuntansi, 2019)
This research has a purpose, namely to prove empirically the impact of managerial ownership, institutional ownership, growth, cash holding, capital structure and profitability on firm value. This research used secondary data. This research was selected data with purposive sampling technique. This research was conducted on manufacturing companies listed in Indonesian Stock Exchange (IDX) during the year 2014 – 2017. The entire sample used in this research is 75 data from manufacturing companies. The research data is processed with E-views version 9.0. The result of this this research shows that managerial ownership, institutional ownership, growth, cash holding and capital structure has no significant on firm value. Profitability has a positive effect and significant on firm value